Managing Tourism and Hospitality Services: Theory and International Applications - Prideaux, Bruce (CABI, 2014)
Managing Tourism and Hospitality Services is the result of extended discussions between the three editors about their own research interests, and between them and colleagues in many countries about activities they have been engaged in. It became apparent that there are some important convergences in tourism and hospitality research, particularly as it relates to the study of service management in these still new and still rapidly developing sectors. In this book, the editors have presented a range of current research which individually records the commitment and application of the contributors, but taken together the collection of work provides a benchmark of current understanding, and examines the range of research methods being applied to further deepen the understanding of tourism and hospitality service management research. It is not our belief that this book is a definitive statement of research into this area, rather we hope that it will inspire present and future researchers to consider how to further advance the frontiers of tourism and hospitality research.